The effectiveness of a squash eyewear promotion strategy. Issue 9 (23rd August 2005) - Eime, R; Finch, C; Wolfe, R; Owen, N; McCarty, C
Abstract : Objective: To evaluate the protective eyewear promotion (PEP) project, which was a comprehensive educational strategy to increase the use of appropriate protective eyewear by squash players. Methods: An ecological study design was used. Four squash venues in one playing association were randomly chosen to receive PEP and four in another association maintained usual practice and hence formed a control group. The primary evaluation measurements were surveys of cross sectional samples of players carried out before and after the intervention. The surveys investigated players' knowledge, behaviours, and attitudes associated with the use of protective eyewear. The survey carried out after the intervention also determined players' exposure to PEP. Univariate and multivariate analyses were undertaken to describe differences at PEP venues from pre- to post-intervention and to compare these with the control venues. Results: The PEP players had 2.4 times the odds (95% confidence interval, 1.3 to 4.2) of wearing appropriate eyewear compared with control group players post-intervention, relative to the groups' pre-intervention baselines. Components of PEP, such as stickers and posters and the availability and prominent positioning of the project eyewear, were found to contribute to players adopting favourable eyewear behaviours. Conclusions: Components of the PEP intervention were shown to be effective. The true success will be the sustainability and dissemination of the project, favourable eyewear behaviours, and evidence of the prevention of eye injuries long into the future.